Arguments for and against the Immortality and Eternity of Soul: A Critical Analysis - ghasem pour hasan (حکمت و فلسفه, 2009)
In philosophy of religion, the most important issue in the eternity of soul deals with the study and analysis of arguments for and against the substantiality of soul, eternity, and immortality. A group of philosophers tried to formulate the reasons and evidence for eternity through the substantiality of soul. Another group tried to reject the destructibility of soul by proving the abstractness of soul. While briefly introducing the basic concepts, this article attempts to focus on the theories that criticize the eternity of soul, as well as investigating the reasons against immortality; then these reasons are described, criticized and finally rejected. Hume, Russell, and Antony Felw are the three philosophers whose thoughts on "the reasons and evidence against the eternity of soul" have been studied, criticized, and rejected here. Hume provides three groups of reasons against the eternity of soul that are entirely welcomed and attended by Felw. Some of these arguments merely analyze and discuss the verification of the substance of soul, some of them reject the indestructibility and abstractness of the soul, and the third group criticize eternity and persistence. The author of this work has categorized the subject upon the typology of the reasons against eternity in three groups, and analyzes them from a critical perspective.